Energy-Aware Dynamic VM Selection With Perfect Workflow Time Scheduling Algorithm - S.Boopalan, Dr. Puneet Goswami (International Journal of Advanced Science and Technology, 2020)
Efficient scheduling workflow for cloud management is proposed here resource provisioning and scheduling heuristics may have different objectives. This work focuses on both energy efficient supervision of virtual machine and finding a perfect time schedule to execute a workflow in data centres on IaaS computing resources such that the total execution cost is minimized and the deadline is met. Depends on the CPU utilisation the server power consumption is computed in large scale data centres. By detecting and consolidating active VM host and executing the workflow on basis of perfect time scheduler brings out good energy balancing environment with required Quality of Service.